Synthesis, characterization and antimicrobial effect of Cu(ii) and Zn(ii) compounds derived from 1,2,4-triazoles - Patricia Saraiva Vilas Boas de Almeida; José Roberto da Silveira Maia; Mariana Caliman Falqueto; Leandro Licursi de Oliveira (The Journal of Engineering and Exact Sciences)
Compounds of Cu(II) and Zn(II) with 3-R-1H-1,2,4-triazole-5-amine {R = methyl (mta), phenyl (pta)} were prepared and characterized by infrared spectroscopy (IR), multinuclear NMR (1H, 13C), electronic spectroscopy (UV-VIS), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), microanalyses and melting point. Dimeric, monomeric, and polymeric materials were synthesized in this work. The Zn(II)-1,2,4-triazole derivatives have the metal ion at the center of two geometric arrangements, being a tetrahedron for the complex-7 and 9, and an octahedron for the complex-8. The only polymeric material, complex-7, was characterized by the DSC analytical data. The Decomposition reaction of complex-8 in chloroform produced the complex-9, a aminoguanidine derivative, and the Zn(II)-benzoate compound. The IR and UV-VIS of Cu(II)-mta derivatives revealed two possible geometric patterns for the metallic ion; a distorted bipyramidal trigonal geometry for compounds 10 and 11 in solution, and in the solid state, the same geometry for complex-10, but for complex-11, the IR data suggest a distorted octahedral geometry. The biological assay of the 1,2,4-triazole compounds and their metal derivatives against Gram-positive and Gram-negative bacteria shown the compounds of Zn(II) as the only active materials with values of MIC within the range of 133.5 µM (83.3 µg / mL) to 360.7 µM (166.6 µg / mL).